The Anti sliding Mechanism of Adjacent Pile-Anchor Structure considering Traffic Load on Slope Top - Danfeng Li; Zhuojie Zhang (Advances in Civil Engineering)
In view of the fact that the anti sliding effect analysis of the current anchor cable and anti slide pile structure is not yet complete, research on the synergy mechanism of adjacent pile-anchor composite structures under traffic load is carried out. Firstly, a free vibration analysis for the slope dynamic model is carried out by using a three-dimensional finite element numerical simulation method. By improving the slope boundary conditions of time-domain analysis, the time-domain equation of the dynamic model of traffic load acting on the top of the slope is solved accurately, and the response law of the internal force of the pile anchor composite structure is also described. The mechanism by which the pile anchor composite structure resists against the slope sliding through the internal force increment is proposed: this internal force increment is estimated to be 73.4%, while that of anchor cable is 26.6%. The composite structure presents the coordinated sharing for sliding force. The internal force of the lower row of anchor cables is 89.48 kN larger than that of the upper row, and the internal force increment is four times larger, indicating that the lower anchor cable is more effective in slope reinforcement. As the deformation at the top of the slope is greater, the prestress of the upper anchor cable should be increased to avoid the “chain failure” caused by excessive deformation. As a result, the coordination law of internal force of pile anchor is revealed, and the anti sliding sharing mechanism is clarified. A design idea of the adjacent pile-anchor composite structure is proposed, which takes 0.2‐0.3 times the remaining sliding force as the design value of prestressed anchor cable. The idea fully considers the anti sliding effect of prestressed anchor cables and reduces the design size of anti slide pile section, providing a theoretical support for optimization design of combined anti slide structure and saving project investment.